2013 IEEE 25th Symposium on Fusion Engineering (SOFE) 2013
DOI: 10.1109/sofe.2013.6635342
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between simulations using the PHITS code and activated materials analysis toward JT-60SA radiation safety assessment

Abstract: In the present study, a comparison between simulations using the PHITS code and activated material analysis of JT-60U have been performed. Neutron transport has been simulated using the Monte Carlo methods PHITS to determine the neutron fluency at the irradiation position. The activated analysis has been complemented by the foil-activation technique. The preliminary accuracy assessment of these PHITS simulations has been confirmed by comparing the reaction rates of gold, cobalt, and nickel foil activation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Recently, 3D Monte Ca rlo transport codes have been powerful tools to simulate the neutron flux distribution in the real co nfiguration. It was reported that the 3D Monte Carlo neutron transport code well explained the activation of the samples on JT-60U [10]. Therefore, the simulation of the neutron flux distribution may give the area information for the clearance level.…”
Section: Simulation Neutron Flux Profilementioning
confidence: 96%
“…Recently, 3D Monte Ca rlo transport codes have been powerful tools to simulate the neutron flux distribution in the real co nfiguration. It was reported that the 3D Monte Carlo neutron transport code well explained the activation of the samples on JT-60U [10]. Therefore, the simulation of the neutron flux distribution may give the area information for the clearance level.…”
Section: Simulation Neutron Flux Profilementioning
confidence: 96%